An evaluation of association between common variants in C4BPB/C4BPA genes and schizophrenia. (17th March 2015) - Wang, Shuihong; Lu, Houquan; Ni, Jianliang; Zhang, Jiangtao; Tang, Wenxin; Lu, Weihong; Cai, Jun; Zhang, Chen
Highlights: This is the first genetic study to address the association of C4BPB and C4BPA with schizophrenia. Nine C4BPB / C4BPA polymorphisms were analyzed in Han Chinese with and without schizophrenia. Our results provided preliminary evidence that C4BPB / C4BPA may not confer susceptibility to schizophrenia among Han Chinese. Abstract: Epidemiological studies have indicated that both maternal bacterial and viral infections during pregnancy increase the risk of schizophrenia among offspring, but to date there is not clear explanation for this increased risk. Previously, the decreased C4b-binding protein (C4BP), a potent circulating soluble inhibitor of the classical and lectin pathways of complement, was reported to be associated with risk of schizophrenia. Here, we analyzed 4 common single nucleotide polymorphisms (SNPs) of C4BPB and 5 SNPs of C4BPA in a group of 556 schizophrenia patients and a matched group of 610 healthy controls to see if the genes C4BPB and C4BPA, which encode C4BP, may confer a susceptibility to schizophrenia. Comparing the genotype and allele frequencies of those SNPs between cases and controls, we found no association between the C4BPB / C4BPA variants and schizophrenia. Our results provided preliminary evidence that C4BPB / C4BPA may not confer susceptibility to schizophrenia among Han Chinese. Further genetic studies from large-scale population are required to obtain more conclusive results.